(untitled) - Brubaker, Sterling (Baltimore, 1967)
This book introduce the trends of aluminum consumption and production. Future demand for aluminum, basic technology of the aluminum industry. Structure of the international industry, trade and trade policies, elements of the cost structure of the industry...
Keywords: Thương mại và công nghiệp nhôm,Aluminum industry and trade